Isomerization of Gibberellic Acid During the Brewing Process. Issue 6 (8th May 2019) - Sun, Weikang; Liu, Chunfeng; Duan, Hongxu; Niu, Chengtuo; Wang, Jinjing; Zheng, Feiyun; Li, Yongxian; Li, Qi
Abstract : Abstract: Gibberellic acid (GA3) was added to three types of beer barley, and the chemical changes to GA3 during the beer brewing process were studied using HPLC. The results demonstrated that the GA3 concentration decreased throughout the malting, mashing, and boiling processes and that no GA3 was detected in the congress wort. A new substance, herein called Substance A, was detected by HPLC analysis using a C18 column; this substance exhibited retention characteristics different from GA3. The concentration of Substance A increased throughout the malting, mashing, and boiling processes. Mass spectrometry revealed that Substance A has the same molecular weight as GA3 and nuclear magnetic resonance studies determined that Substance A is a structural isomer of GA3. Practical Application: This study developed a new idea to understand GA3 behavior during the brewing, which provided a practical reference for food safety in beer and other fields using GA3 as a food additive.